Efficiency and equilibria in games of optimal derivative design - Ulrich Horst; Santiago Moreno-Bromberg (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
In this paper the problem of optimal derivative design, profit maximization and risk minimization under adverse selection when multiple agencies compete for the business of a continuum of heterogenous agents is studied. In contrast with the principal-agent models that are extended within, here the presence of ties in the agents' best-response correspondences yields discontinuous payoff functions for the agencies. These discontinuities are dealt with via efficient tie-breaking rules. The main results of this paper are a proof of existence of (mixed-strategies) Nash equilibria in the case of profit-maximizing agencies, and of socially efficient allocations when the firms are risk minimizers. It is also shown that in the particular case of the entropic risk measure, there exists an efficient 'fix-mix' tie-breaking rule, in which case firms share the whole market over given proportions.
Keywords: C62; C72; D43; D82; G14; 330; adverse selection; Nash equilibria; Pareto optimality; risk transfer; socially efficient allocations; tie-breaking rules; Finanzderivat; Pareto-Optimum; Adverse Selection; Nichtkooperatives Spiel; Nash-Gleichgewicht; Theorie